Implications of shadow ban regulation for monetary policy at the zero lower bound - Falk Mazelis (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2016)
Counter to the credit channel of monetary transmission, monetary policy tightening induces a rise in lending by two different types of non-bank financial institutions (NBFI): shadow banks and investment funds. A monetary DSGE model is able to replicate the empirical facts when augmented with intermediaries that allow for regulatory arbitrage on the one hand, and household portfolio rebalancing on the other. Therefore NBFI reduce the e ectiveness of the bank lending channel, which posits a decrease in bank lending following monetary tightening. Given the pending regulation of the financial system, I study how regulation of the shadow banking sector may affect the monetary transmission mechanism, especially during a zero lower bound (ZLB) episode. I find that bringing shadow banks back onto the balance sheets of commercial banks is beneficial for consumption smoothing. Alternatively, regulating them like investment funds results in a milder recession during, and a quicker escape from, the ZLB. This is because a large demand shock that moves the economy to the ZLB acts in a similar way to a monetary tightening due to the inability to lower the policy rate to the unconstrained level. Consequently, the bank lending channel becomes operational and its effectiveness can be reduced via less reliance on deposit funding.
Keywords: E32; E44; E52; G11; 330; Shadow Banking; Zero Lower Bound; Monetary Policy; Bank Lending Channel; Bayesian Methods; Search Frictions